Hygrothermal effects on the translaminar fracture toughness of cross-ply carbon/epoxy laminates: Failure mechanisms. (18th January 2016) - Marín, L.; González, E.V.; Maimí, P.; Trias, D.; Camanho, P.P.
Abstract: The present work addresses the damage mechanisms of polymer-based laminated composite materials under different hygrothermal conditions by means of the translaminar fracture toughness using Double Edge Notched Tensile tests of a cross-ply laminate manufactured with T800S/M21 carbon/epoxy material. Three different conditions were considered: as received-room temperature (AR/RT), wet-room temperature (WET/RT), and wet-high temperature (WET/HOT). The highest fracture toughness was for WET/HOT and the lowest for WET/RT. To observe the corresponding failure mechanisms, Scanning Electronic Microscopy (SEM) analysis was performed. The SEM inspections show that the pull-out length and the frictional coefficient are the most significant parameters that best explain the differences observed in the crack propagation and the fracture toughness. For AR/RT, the suitable adhesion between components allows stresses to be transferred from the matrix to the fibers, so the crack is practically continuous in the same failure plane and the pull-out is barely visible. However, higher pull-out lengths can be observed in WET/RT and WET/HOT, especially in the second one. For WET/RT, the crack surface shows fiber bundles at different pull-out lengths, while for WET/HOT fibers are broken individually at longer pull-out lengths. According to the moisture absorption in WET/RT and WET/HOT, a lower frictional coefficient is thought to slightly reduce the fracture toughness, which can be compared between AR/RT and WET/RT. Nevertheless, the highest fracture toughness is caused by the large pull-out lengths in WET/HOT tests, despite the reduction of the frictional coefficient.